2016
DOI: 10.1108/ijem-10-2015-0147
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical reforms within a centralised-decentralised system

Abstract: Purpose The purpose of this paper is to illustrate the dialectical interplay between centralisation and decentralisation forces so as to understand how schools leverage on its autonomous pedagogical space, influence the diffusion of innovations in the educational landscape of Singapore and how a centralised-decentralised system supports (or impedes) pedagogical reform for twenty-first century learning. Design/methodology/approach The paper first outlines the evolutionary stance of Singapore’s decentralisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…However, from a learning and teaching perspective, the broader issue, as pointed out by some teaching academics, was how the notion of centralising resources could stifle innovation, which can in turn affect learning and teaching processes. This finding is consistent with that of Toh et al (2016) who suggested that such centralisation practice engenders perceptions of policing, which could stifle innovation. This then raises questions about the legitimacy of centralising learning technologies and their support services.…”
Section: Discussionsupporting
confidence: 90%
“…However, from a learning and teaching perspective, the broader issue, as pointed out by some teaching academics, was how the notion of centralising resources could stifle innovation, which can in turn affect learning and teaching processes. This finding is consistent with that of Toh et al (2016) who suggested that such centralisation practice engenders perceptions of policing, which could stifle innovation. This then raises questions about the legitimacy of centralising learning technologies and their support services.…”
Section: Discussionsupporting
confidence: 90%
“…A third value that underpins Singapore school leadership is the emphasis on systems-level coherence (Dimmock and Tan, 2013;Harris et al, 2014;Raveendaran et al, 2018;Toh, 2016;Toh et al, 2016;Toh et al, 2014). Some scholars credit Singapore's educational effectiveness to the tightlycoupled school system, mutually reinforcing human resource policies, and a distinctive leaderteacher compact premised on paternalistic leadership.…”
Section: Emphasis On Systems-level Coherence: Ecological Leadershipmentioning
confidence: 99%
“…National Institute of Education, Singapore Singapore's educational journey and success in international rankings such as PISA and TIMSS has been studied extensively, sometimes by external observers (Barber et al, 2007;Jensen et al, 2012) and sometimes by Singaporean and Singapore-based researchers (Ng, 2010(Ng, , 2016Dimmock and Tan, 2012;Tan, Low and Hung, 2017;Lee et al, 2014;Toh et al, 2016;Koh and Hung, 2018). It is not the intention to reiterate or discuss the broader findings from those studies in any detail here, but headline considerations include: Singapore's small size (356 schools in total), its tight central bureaucratic control exercised by a single political party, and its pragmatic focus on efficiency and effectiveness in the context of a need for rapid nation-building and economic development through human capital.…”
Section: Context and History In The Three Systemsmentioning
confidence: 99%